2022
DOI: 10.3390/life12060914
|View full text |Cite
|
Sign up to set email alerts
|

Licorice Extract Supplementation Affects Antioxidant Activity, Growth-Related Genes, Lipid Metabolism, and Immune Markers in Broiler Chickens

Abstract: The objective of this study was to evaluate the Glycyrrhiza glabra effect on growth performance, blood parameters, antioxidant and lysosomal activity, histology and immunohistochemistry of liver and intestine, and the gene expression profile of broiler chickens. A total of 180 Cobb500 broiler chicks (one-week-old) were used in this study. Chicks were distributed randomly into three treatment groups; the first group received drinking water without any supplementation (control group). In contrast, birds in group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Yin et al ( 59 ) found that adding LBPs to the diet could increase the serum total antioxidant capacity (T-AOC) and GSH-Px activity, and decrease the MDA level ( p < 0.05). Abo-Samaha et al ( 61 ) found that adding licorice (0.4 g/L and 0.8 g/L) to drinking water resulted in antioxidant activity, leading to a reduction in MDA levels and an increase in GSH levels and CAT activity. Various active ingredients in thyme, Astragalus, tangerine peel and dandelion have been shown to reduce the effects of peroxides on animal bodies and enhance the body’s antioxidant capacity ( 62–64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al ( 59 ) found that adding LBPs to the diet could increase the serum total antioxidant capacity (T-AOC) and GSH-Px activity, and decrease the MDA level ( p < 0.05). Abo-Samaha et al ( 61 ) found that adding licorice (0.4 g/L and 0.8 g/L) to drinking water resulted in antioxidant activity, leading to a reduction in MDA levels and an increase in GSH levels and CAT activity. Various active ingredients in thyme, Astragalus, tangerine peel and dandelion have been shown to reduce the effects of peroxides on animal bodies and enhance the body’s antioxidant capacity ( 62–64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that GPs can promote the development of immune organs and stimulate the continuous proliferation of spleen macrophages, significantly increase the levels of IgA, IgM, and IgG in the serum, and significantly reduce the levels of TNF-α, IL-1β, IL-6, and DAO to induce an immune response, thereby improving the immune function of the body ( 162 164 ). In a study on the antioxidation capacity of GPs, the direct addition of 1000 or 1500 mg/kg GPs to chicken diets significantly increased the T-SOD activity and decreased the serum MDA content ( 165 ). Similarly, the antioxidant effect of GPs plays a significant role in reversing oxidative stress induced by LPS and can reduce the increase in IL-1β and IFN-γ in the liver induced by LPS ( 166 ).…”
Section: Plant Polysaccharidementioning
confidence: 99%
“…In addition, GPs significantly alleviated oxidative stress in broilers induced by mycotoxins, significantly decreased the activities of ALP, AST, and ALT and the concentration of MDA, and increased the concentration of serum total protein and albumin, thus alleviating liver injury ( 167 ). In intestinal immunity, dietary GPs can significantly increase the villus height and the ratio of villus height to crypt depth ( 163 , 165 ) and significantly upregulate the mRNA expression of tight junction proteins (occludin), junction adhesion molecules (JAM), glucagon-like peptides-2 (GLP-2), fatty acid binding protein 6 (FABP-6), and mucin-2 (MUC-2) in the intestine ( 142 , 164 ). Similarly, GPs can significantly reduce the number of Escherichia coli and Salmonella in poultry intestines, thereby enhancing intestinal immunity and maintaining healthy intestinal microorganisms ( 161 ).…”
Section: Plant Polysaccharidementioning
confidence: 99%
“…In contrast, the rats intoxicated with Estradiol® (0.2 mg/kg/weekly) only for a similar period showed a significant increase, when all were compared to normal rats. (Abo-Samaha et al ., 2022) hepato-protection against hepatotoxins. The presence of these certain compounds in Nigella Stevia and Licorice is the reason for the protective effects of rat's liver (Hannan, et al, 2021).…”
Section: Gross Chemical Composition and Caloric Value Of Nigella Stev...mentioning
confidence: 99%